HIJRAH AND POP CULTURE: HIJAB AND OTHER MUSLIM FASHIONS AMONG STUDENTS IN LOMBOK, WEST NUSA TENGGARA - M. Taufik; Amalia Taufik (Teosofia: Indonesian Journal of Islamic Mysticism, 2019)
The development of Islamic society in the millennial era in Indonesia today is quite dynamic. Education progress is one of the road graders for their vertical mobility. At the next level, this progress significantly led to a community that came to be known as the Muslim middle class, which offered features and dynamics of Islamic life that integrated with modernity. Further development, a millennial generation emerged that was triggered by the advancement of information-communication technology, along with the growth of new traditions known as Islamic popular culture, including the Hijrah trend. This study wants to look at the trends of Hijrah and the background of the reconstruction of the identity of millennial Muslim generations while at the same time able to blend in with modernity at state universities in Lombok. The paradigm used is a qualitative paradigm based on field research. The results of this study indicate that the Hijrah attribute that is trending among Lombok millennials is the wear of fashionable syar'i clothing such as veils with various models and colours, syar'i veils, fashionable headscarves, increased observance of worship, Islamic quotes on social media accounts, and lengthening the beard.